Experimental response of FRP reinforced members without transverse reinforcement: Failure modes and design issues. (15th March 2016) - Acciai, Andrea; D'Ambrisi, Angelo; De Stefano, Mario; Feo, Luciano; Focacci, Francesco; Nudo, Raffaele
Abstract: FRP reinforcement is well known as a possible alternative to steel bars in order to improve durability of reinforced concrete members. However, the intrinsic brittleness of concrete and FRP materials may induce problems at the ultimate conditions due to premature failure modes; the performance under service loads is a critical issue as well. To investigate response of concrete members reinforced with longitudinal glass or carbon FRP bars without shear reinforcement, an experimental program has been developed. The sixteen specimens designed and cast within this project were characterized by different study variables concerning cross section geometry, concrete grade and type of reinforcement. The results of tests performed on FRP-reinforced specimens are presented in this paper. In particular, different failure modes due to flexure and shear have been observed; response under load levels simulating service conditions has been also examined. Results of FRP-reinforced specimens have been compared with those given by control specimens provided with conventional steel bars. Finally, analytical procedures to evaluate immediate deflections of FRP-reinforced members have been assessed.